2014
DOI: 10.1155/2014/807308
|View full text |Cite
|
Sign up to set email alerts
|

Mild Moxibustion Decreases the Expression of Prokineticin 2 and Prokineticin Receptor 2 in the Colon and Spinal Cord of Rats with Irritable Bowel Syndrome

Abstract: It has been proven that prokineticin 2 (PK2) and its receptor PKR2 play an important role in hyperalgesia, while mild moxibustion can relieve visceral hypersensitivity in a rat model of irritable bowel syndrome (IBS). The goal of the present study was to determine the effects of mild moxibustion on the expression of PK2 and PKR2 in colon and spinal cord in IBS rat model, which was induced by colorectal distension using inflatable balloons. After mild moxibustion treatment, abdominal withdrawal reflex (AWR) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
4
0
1
Order By: Relevance
“…The expression of PKR1 in the urothelium is upregulated after CYP treatment, as indicated by our IHC data, as a response to inflammatory stimulation ( Figure 2 ). Similar results were reported in studies on other tissues, including the epithelium, under physiological and/or pathological conditions [ 25 , 29 31 ]. CYP administration can cause immune cells to infiltrate into the bladder wall, suggesting that the immigrating and activated immune cells possibly contribute to the overexpression of PKR1 in cystitis as PKR1 is expressed on these cells.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of PKR1 in the urothelium is upregulated after CYP treatment, as indicated by our IHC data, as a response to inflammatory stimulation ( Figure 2 ). Similar results were reported in studies on other tissues, including the epithelium, under physiological and/or pathological conditions [ 25 , 29 31 ]. CYP administration can cause immune cells to infiltrate into the bladder wall, suggesting that the immigrating and activated immune cells possibly contribute to the overexpression of PKR1 in cystitis as PKR1 is expressed on these cells.…”
Section: Discussionsupporting
confidence: 90%
“…It activates the PKs receptors in the spinal dorsal horn and astrocytes, thereby promoting central sensitization and maintaining chronic and neuropathic pain ( Negri and Maftei, 2018 ). Two studies on mild moxibustion revealed that ST25 can inhibit the protein and mRNA expression of PK1/Prokineticin receptor (PKR) 1 and PK2/PKR2 in the spinal cord of IBS rats, respectively ( Zhao et al, 2012 ; Zhou et al, 2014 ). These findings suggest that acupuncture may exert its effects by suppressing the activity of central glial cells by inhibiting P2X7 and PKs pathways in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that in intestinal inflammatory pathways PK1/PKR1 might be a possible trigger, promoting, in loco, the recruitment of immune cells and inducing pro-inflammatory cytokine production. Subsequently, the role of the PKS in visceral pain was also investigated by Wu's research group [52,103]. A model of visceral hypersensitivity induced via chronic and repetitive colorectal distension (CCD) in rats was used in both of these studies.…”
Section: Evidence Of the Pks In Pain: Focus On Ibd Modelmentioning
confidence: 99%